Strategi Komunikasi Digital Himpunan Mahasiswa Muhammadiyah dalam Mempromosikan Bank Sampah di Bengkulu - Hafri Yuliani; Reni Kusmiarti (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
Indonesia's waste problem continues to grow, with total waste generation reaching 21.1 million tons in 2024. Bengkulu City faces similar challenges, with only around 30% of sub-districts having active waste banks and low community participation rates of 15-20%. In the digital era, social media-based communication has become an important instrument for community mobilization; however, limited studies have specifically explored the role of student organizations in empowering waste bank programs through digital platforms. This study aims to: (1) analyze the digital communication strategy of the Muhammadiyah Student Association (IMM) of FISIP Universitas Muhammadiyah Bengkulu in waste bank empowerment; (2) identify the digital platforms and content types utilized; and (3) evaluate the effectiveness of digital communication in raising public awareness and participation. The study employed a qualitative descriptive approach, collecting data through in-depth interviews, participatory observation, document analysis, and Focus Group Discussions (FGDs) involving 10 purposively selected participants. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014), with source, method, theoretical, and researcher triangulation applied to ensure data validity. The average engagement rate for waste bank content reached 8.7%, surpassing the 4-6% engagement rate of other content types. The distinctive feature of IMM's strategy lies in its integration of Islamic and Muhammadiyah values as message framing, alongside community-based social marketing principles that emphasize active audience participation. This study contributes to the development of a values-based digital communication model for environmental empowerment at the local level.